Antibiotic Susceptibility of Clinical and Environmental Isolates of Pseudomonas aeruginosa - Mijeed Neama Ali; Ayaid Khadem Zgair (World Journal of Experimental Biosciences, 2014)
Pseudomonas aeruginosa isolates resistant to several antibiotics. These bacteria are responsible for different disease in patients suffering from immune suppressive diseases. The ability of these isolates to resist several antibiotics is variable according to different factors. In present study, many isolates of P. aeruginosa were isolated from sputum of patients suffering from respiratory tract infection (PAC1, PAC2, PAC3, PAC4, and PAC5) and isolated from soil contaminated with oil products (PAE1, PAE2, PAE3, PAE4, PAE5, PAE6, PAE7, and PAE8). Susceptibility of these isolates to several antibiotics (ampicillin, amoxicillin/clavulanic acid, ampicillin/Sulbactam, piperacillin/tazobactam, cefazolin, ceftazidime, ceftriaxone, cefepime, imipenem, gentamicin, tobramycin, ciprofloxacin, levofloxacin, nitrofurantoin, trimethoprim/sulfamethoxazole, tricarcillin, and amikacin). VITEK 2 DensiCheck instrument (bioMe´rieux) was used to check the susceptibility of clinical and environmental isolates. The current study showed that the clinical isolates were resisted to higher number of antibiotics as compared with environmental isolates. The Minimum inhibition concentration (MIC) of antibiotics was high for clinical isolates as compared with environmental isolates. Imipenem was the highest effective antibiotic against all clinical and environmental isolates of P. aeruginosa. It can be concluded from current study that the clinical isolates are high resistant to antibiotics as compared to environmental isolates of P. aeruginosa and all isolates was sensitive to imipenem.
Keywords: Antibiotics; Clinical Isolates; Environmental isolates; Pseudomonas aeruginosa; Resistance; Sensitivity.